Elaboration of a methodology for integral estimation of ecological state of territories - Белогуров, Виктор Петрович (Eastern-European Journal of Enterprise Technologies, 2014)
Ecological state of the territories is usually estimated by determining the belongingness of each of the geosphere ecological state indicators to one of the classes. The developed methodology is characterized by the fact that the estimates are distributed according to the classes not uniformly, but taking into account the normalization principles and Liebig's law; integral estimate is calculated in accordance with the hypothesis on the logistic nature of the ecosystem change. The methodology allows to determine the integral estimates objectively (without the participation of experts) by calculations according to official data (annual country reports) using a thoroughly structured procedure, which allows to monitor the contribution of each indicator to the overall estimate. The results are presented in the form of maps and attribute tables for geospheres and territory as a whole, and are suitable for management.